Critical Health Communication Method as Embodied Practice of Resistance: Culturally Centering Structural Transformation Through Struggle for Voice - Dutta, Mohan; Pandi, Asha Rathina; Zapata, Dazzelyn; Mahtani, Raksha; Falnikar, Ashwini; Tan, Naomi; Thaker, Jagadish; Pitaloka, Dyah; Dutta, Uttaran; Luk, Pauline; Sun, Kang (Frontiers in Communication, 2019)
The Marxist roots of critical methodology envision method as anchor to an emancipatory politics that seeks structural transformation. Drawing on our negotiations of carrying out culture-centered health communication projects amidst neoliberal authoritarianism, we explore the nature of academic-activist-community collaborations in envisioning democratic infrastructures for socialist organizing of health. Method is thus inverted from the hegemonic structures of Whiteness that construct extractive relationships perpetuating existing and entrenched health inequities to partnerships of solidarity with subaltern communities committed to a politics of “placing the body on the line.” We work through the concept of “placing the body on the line” to depict the ways in which the body of the academic, turned vulnerable and weaponized in active resistance to neocolonial/capitalist structures, disrupts the hegemonic logics of power and control that shape health within these structures. Examples of culture-centered projects at the global margins offer conceptual bases for theorizing embodied practice as resistance to state-market structures that produce health injustices. The body of the academic as a methodological site decolonizes the capitalist framework of knowledge production through its voicing of an openly resistive politics that stands in defiance to the neoliberal structures that produce health inequities. We challenge the communication literature on micro-practices of resistance, interrogating concepts such as “strategic ambiguity,” “pragmatic interventionism” and “practical engagement” to offer method as embodied practice of open/public resistance, as direct antagonism to state-market structures. Through the re-working of method as embodied resistance that is explicitly socialist in its commitment to imagining health, culture-centered interventions imagine and practice Marxist advocacy and activist interventions that disrupt the intertwined hegemonic logics of capital and empire.